2011
DOI: 10.1590/s0066-782x2011005000024
|View full text |Cite
|
Sign up to set email alerts
|

Equações de referência para o teste de caminhada de seis minutos em indivíduos saudáveis

Abstract: The six-minute walk test (6MWT) has been broadly used in clinical settings. Several reference equations for prediction of the total distance walked during the test (6MWD) are available in literature. The present review aimed to critically discuss studies, published in Portuguese and English (LILACS, SCIELO, MEDLINE, PUBMED), which evaluated normal values and created reference equations for predicting 6MWD in healthy subjects, comparing them with the results that were recently obtained in Brazilian individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 42 publications
0
17
0
13
Order By: Relevance
“…Similar results were reported by Soares et al 24 , when they evaluated the applicability of the same equation for Brazilian healthy individuals. As great part of the variability of the observed results, during the application of 6MWT, is due to the population diversity, the use of Brazilian equations 25 are suggested. Therefore, the equation proposed by Iwama et al 19 , verified that the control group walked, on average, 98.55% of the expected D6MWT (p=0.68).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Soares et al 24 , when they evaluated the applicability of the same equation for Brazilian healthy individuals. As great part of the variability of the observed results, during the application of 6MWT, is due to the population diversity, the use of Brazilian equations 25 are suggested. Therefore, the equation proposed by Iwama et al 19 , verified that the control group walked, on average, 98.55% of the expected D6MWT (p=0.68).…”
Section: Discussionmentioning
confidence: 99%
“…Mean exercise intensity (%max HR) varied from 44% to 81% between studies that reported this outcome [191]. Exercise intensity may be influenced by the technician and by the patient's motivation.…”
Section: Exercise Intensitymentioning
confidence: 99%
“…There are numerous healthy norms for the 6MWT available and it is unclear which of these would be most appropriate to compare with people with SMA. Moreover, reference equations from various normative data sets for the 6MWT in healthy people have not been compared with 6MWDs in people with SMA, including the normative reference equations most widely used in clinical populations .…”
Section: Introductionmentioning
confidence: 99%